Efficacy and safety of botulinum toxin-A injection in the treatment of premature ejaculation: A systematic review and meta-analysis - Yicheng Guo; Fengze Sun; Yini Wang; Yanfei Li; Tianqi Wang; Xiaohong Ma; Jitao Wu (PLoS ONE, 2025)
Introduction Premature ejaculation (PE) is a common male sexual dysfunction, impacting sexual satisfaction and quality of life. Botulinum toxin-A (BoNT-A), known for its muscle-relaxing properties, has been proposed as a treatment for PE, but its efficacy and safety remain uncertain. Objectives To systematically evaluate the efficacy and safety of BoNT-A injection compared to placebo for treating PE. Methods A comprehensive search of PubMed, EMBASE, and Cochrane databases was conducted to identify randomized controlled trials comparing BoNT-A and placebo in treating PE. Primary outcomes included intravaginal ejaculatory latency time (IELT) and premature ejaculation profile (PEP), while sexual satisfaction score was a secondary outcome. Mean differences (MD) with 95% confidence intervals (CI) and odds ratios (OR) for adverse events were calculated using a random-effects model. Results Three studies were included in the analysis. BoNT-A significantly increased IELT and PEP at the 1-month follow-up (MD = 22.32; 95% CI = 10.83–33.82; P = 0.001 for IELT; MD = 0.91; 95% CI = 0.41–1.42; P < 0.001 for PEP), but no significant differences were observed at 3-month and 6-month follow-ups (P > 0.05). No significant improvements in sexual satisfaction were found (P = 0.32). BoNT-A was associated with a higher incidence of adverse events compared to placebo (OR = 5.90; 95% CI = 1.29–26.89; P = 0.02), but no significant differences were observed for drippling or erectile dysfunction (P > 0.05). Conclusion BoNT-A injections may be an effective short-term treatment for PE, significantly improving IELT and PEP at 1-month follow-up. However, the effects appear to diminish over time, and no significant improvement in sexual satisfaction was observed. BoNT-A is associated with a higher rate of adverse events, but does not increase the risk of drippling or erectile dysfunction. Further studies with longer follow-up periods are needed to assess long-term efficacy and safety.